2015
DOI: 10.1038/srep10554
|View full text |Cite
|
Sign up to set email alerts
|

The Local CNP/GC-B system in growth plate is responsible for physiological endochondral bone growth

Abstract: Recent studies revealed C-type natriuretic peptide (CNP) and its receptor, guanylyl cyclase-B (GC-B) are potent stimulators of endochondral bone growth. As they exist ubiquitously in body, we investigated the physiological role of the local CNP/GC-B in the growth plate on bone growth using cartilage-specific knockout mice. Bones were severely shorter in cartilage-specific CNP or GC-B knockout mice and the extent was almost the same as that in respective systemic knockout mice. Cartilage-specific GC-B knockout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 47 publications
5
66
0
1
Order By: Relevance
“…Together with evidence of a venoarterial CNP gradient across dense bone tissues in growing lambs [19], these findings suggest not only that growth plate tissues make a major contribution to circulating levels of NTproCNP, but also that plasma concentrations are in turn impacted by the activity of these tissues. This conclusion aligns with recent findings from studies using genetic modifications showing that the local (paracrine) CNP signaling pathway in growth plates is responsible for physiological endochondral bone growth [26]. …”
Section: Evidence That Plasma Cnp Products Correlate With Skeletal Grsupporting
confidence: 78%
“…Together with evidence of a venoarterial CNP gradient across dense bone tissues in growing lambs [19], these findings suggest not only that growth plate tissues make a major contribution to circulating levels of NTproCNP, but also that plasma concentrations are in turn impacted by the activity of these tissues. This conclusion aligns with recent findings from studies using genetic modifications showing that the local (paracrine) CNP signaling pathway in growth plates is responsible for physiological endochondral bone growth [26]. …”
Section: Evidence That Plasma Cnp Products Correlate With Skeletal Grsupporting
confidence: 78%
“…13,21 Therefore, to investigate the potential role of GC-B expressed on VSMCs in mediating blood pressure regulation by endothelium-derived CNP, we generated and analyzed GC-B smcKO mice. 8,22,23 We confirmed deletion of the allele using genomic DNA from tail samples ( Figure 4A) and found that expression of GC-B mRNA was, respectively, ≈90% and ≈80% lower in aortas and mesenteric arteries from GC-B smcKO mice than from their control Npr2 flox/flox littermates ( Figure 4B and 4C). Whole body weights and the weights of the heart and kidneys did not differ between GC-B smcKO mice and their control littermates (Table S3).…”
Section: Generation Of Vascular Smooth Muscle Cellspecific Gc-b Knockmentioning
confidence: 50%
“…8,16,17 Using samples from the tails of CNP ecKO (Nppc flox/flox ; Tie2-Cre Tg) mice, we confirmed Cre-mediated recombination of the Nppc-floxed allele ( Figure 1A). In CD31 + pulmonary microvascular endothelial cells collected from the lungs of CNP ecKO mice, we confirmed that CNP mRNA levels were reduced to <10% of that in cells from the control mice (Nppc flox/flox ; Figure 1B).…”
Section: Generation Of Endothelial Cell-specific Cnp Knockout Micementioning
confidence: 62%
See 1 more Smart Citation
“…Mice or humans that overexpress CNP or activate natriuretic peptide receptor 2 (Npr2; guanylyl cyclase B) have a skeletal overgrowth phenotype ( Fig. 2; Yasoda et al 2004;Bocciardi et al 2007;Hannema et al 2013;Miura et al 2014), while mice that lack CNP (Nppc −/− ) or humans with heterozygous mutations in NPR2 exhibit skeletal dwarfism (Tsuji and Kunieda 2005;Nakao et al 2015).…”
Section: Therapeutic Strategies In Achondroplasiamentioning
confidence: 99%